2014
DOI: 10.1109/tdei.2013.004166
|View full text |Cite
|
Sign up to set email alerts
|

Role of interface in highly filled epoxy/BaTiO3nanocomposites. Part II- effect of nanoparticle surface chemistry on processing, thermal expansion, energy storage and breakdown strength of the nanocomposites

Abstract: Highly filled dielectric polymer nanocomposites with high dielectric constant nanoparticles (e.g., BaTiO 3 ) have promising application in many fields such as energy storage. The effectiveness of these nanoparticles to increase the dielectric constant and energy density of the resulting nanocomposites has already been demonstrated. However, the role of interface between the nanoparticles and polymer matrix on thermal expansion, energy storage and breakdown strength-the three parameters that are important for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Of the various approaches used for surface modification, organosilane coupling agents bearing the functional groups reactive with epoxy (e.g., epoxide and amino groups) were often used. We found that the formation of the chemical linkages between the epoxy and BT NPs were critical in the suppression of the aggregation of the inorganic components in the organic matrix . For instance, Iijima et al .…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Of the various approaches used for surface modification, organosilane coupling agents bearing the functional groups reactive with epoxy (e.g., epoxide and amino groups) were often used. We found that the formation of the chemical linkages between the epoxy and BT NPs were critical in the suppression of the aggregation of the inorganic components in the organic matrix . For instance, Iijima et al .…”
Section: Introductionmentioning
confidence: 97%
“…Organic–inorganic epoxy nanocomposites with high dielectric constants have attracted considerable interest in the microelectronics industry because of their easy processing, compatibility with printed wiring boards, and low cost . It has been realized that the dielectric constant of epoxies can be increased through the incorporation of conductive fillers (e.g., carbon nanotubes, metals, conductive polymers or high‐electric‐constant ceramic fillers, such as ZrO 2 , TiO 2 , and BaTiO 3 . Epoxy composites filled with conductive fillers can exhibit high dielectric constants; however, this class of composites can suffer from a very high dielectric loss because of the high electrical conductivity of the fillers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations